Analisis Resepsi Khalayak pada Representasi Maskulinitas Anti-Patriarki dalam Karakter Gwan-sik di Drama Korea When Life Gives You Tangerines - Prasanda Adinda Shelvira; Intan Vicky Azzarah; Fikri Shofin Mubarok; Mubarok Mubarok (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The character Gwan-sik presents a representation of anti-patriarchal masculinity that differs from the dominance patterns commonly depicted in popular media. This drama received diverse responses from the audience; some accepted Gwan-sik as the ideal male representation, while others considered him too ideal and difficult to find in real life. This study aims to determine the audience reception toward the representation of anti-patriarchal masculinity through Gwan-sik's character in the Korean drama When Life Gives You Tangerines. Using a constructivism paradigm and a qualitative descriptive method, this study collected data through in-depth interviews with five Indonesian viewers. The theoretical frameworks used are Stuart Hall's encoding-decoding and R.W. Connell's masculinity theory. The results show that the audience's reception of Gwan-sik's character is positive and diverse, according to their backgrounds. All informants tend to be in a dominant-hegemonic position in interpreting five aspects of Gwan-sik's anti-patriarchal masculinity, namely: equal relations, emotional support, rejection of dominance, sincere sacrifice, and emotional openness. In conclusion, this drama successfully presents a representation of anti-patriarchal masculinity accepted by the Indonesian audience through the negotiation of their respective socio-cultural contexts. Future research is expected to expand the diversity of informants and deepen the study on how Korean drama consumption contributes to shifting norms of gender equality in Indonesia.